2022
DOI: 10.3390/foods11162449
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Identification for Three Arcidae Species (Anadara kagoshimensis, Tegillarca granosa, and Anadara broughtonii) Using Ultrafast PCR Combined with Direct DNA Extraction

Abstract: Granular ark (Tegillarca granosa), broughton’s ribbed ark (Anadara broughtonii), and half-crenate ark (Anadara kagoshimensis) are important fishery resources throughout Asia; granular ark exhibiting a higher economic value due to its rarity. However, due to the similar morphological characteristics of the three species, the less valuable species could be exploited for food fraud. In this study, we developed a rapid on-site identification method based on a microfluidic chip for the detection of the three ark sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Ark clams are important aquaculture species that belongs to the family Arcidae and phylum Mollusca 15 . Owing to their delicious taste and high nutritional value, ark clams have been used as important commercial seafoods in Asian countries, especially in Korea, China, and Japan 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ark clams are important aquaculture species that belongs to the family Arcidae and phylum Mollusca 15 . Owing to their delicious taste and high nutritional value, ark clams have been used as important commercial seafoods in Asian countries, especially in Korea, China, and Japan 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Ark clams are important aquaculture species that belongs to the family Arcidae and phylum Mollusca. 15 Owing to their delicious taste and high nutritional value, ark clams have been used as important commercial seafoods in Asian countries, especially in Korea, China, and Japan. 16 In Korea, Scapharca subcrenata (SS) and Tegillarca granosa (TG) are the two most commonly consumed ark clams, which are favored for the sweetness of the meat with a soft texture.…”
Section: Introductionmentioning
confidence: 99%
“…First, the shells of the ark shells were removed, after which the genomic DNA of the edible portion was extracted using DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany) according to the manufacturer's instructions. Thereafter, T. granosa, A. broughtonii, and A. kagoshimensis were detected using ultrafast PCR with specific primers developed in our previous study (Lee et al, 2022). The primer sequences used for ultrafast PCR are shown in Supplementary Table 1.…”
Section: Identification Of Three Ark Shellsmentioning
confidence: 99%
“…Ark shells belong to the phylum Mollusca, class Bivalvia, order Arcida, and family Arcidae. Among the various ark shell species, granular ark (Tegillarca granosa (Linnaeus, 1758)), broughton's ribbed ark (Anadara broughtonii (Schrenck, 1867)), and halfcrenate ark (Anadara kagoshimensis (Tokunaga, 1906)) are currently commercially important for the fishery industry (Lee et al, 2022) and can be found throughout the Indo-Pacific region. These ark shell species, which live burrowed into sand or mud mainly within the intertidal zone at a depth of 1 to 2 m, play a crucial role in the community structure of coastal ecosystems and as critical economic resources for the fishery and aquaculture industries (Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The most popular DNA-based methods for food authentication include random amplified polymorphic DNA (RAPD), rapid PCR-lateral flow assay, real-time PCR, and multiplex PCR. Each method has its own advantages, disadvantages, and specific applications [11][12][13].…”
Section: Introductionmentioning
confidence: 99%